2022
DOI: 10.1101/2022.06.23.22276819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with the uptake of Intermittent Preventive Treatment (IPTp-SP) for malaria in pregnancy: further analysis of the 2018 Nigeria Demographic and Health Survey

Abstract: Pregnancy-associated malaria is preventable and curable with intermittent preventive treatment with Sulfodoxine-Pyrimethamine (IPTp-SP). However, despite the effectiveness of IPTp-SP against malaria in pregnancy, the uptake among pregnant women in Nigeria remains very low. Thus, this study aimed to establish the factors associated with the uptake of at least one dose and optimal doses of IPTp-SP among pregnant women aged 15 to 49 years living in Nigeria in 2018. The study included 12,742 women aged 15 to 49 ye… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…These regional disparities are consistent with ndings from a previous study by (19), which showed that communitybased education and maternal interventions improved the utilization of maternal healthcare services, including IPTp, in northern Ghana. These regional disparities are also consistent with the results reported in two recent studies in Nigeria (31) and Guinea (35). For the study in Nigeria, the highest optimal SP uptake was observed in the South-East and South-South regions, while the lowest was observed in the North-East and North-West regions.…”
Section: Discussionsupporting
confidence: 92%
“…These regional disparities are consistent with ndings from a previous study by (19), which showed that communitybased education and maternal interventions improved the utilization of maternal healthcare services, including IPTp, in northern Ghana. These regional disparities are also consistent with the results reported in two recent studies in Nigeria (31) and Guinea (35). For the study in Nigeria, the highest optimal SP uptake was observed in the South-East and South-South regions, while the lowest was observed in the North-East and North-West regions.…”
Section: Discussionsupporting
confidence: 92%